Toward culturally sustaining/revitalizing Indigenous family-school-community leadership - Washington, Shaneé A.; Johnson, Lauri (Frontiers in Education, 2023)
2022 was a year of ongoing struggle for families and communities worldwide with social inequalities, colonial legacies, educational setbacks, and health crises perpetuated by the persistent COVID-19 pandemic and White rage and violence toward People of the Global Majority (PGM). Indigenous communities in particular have been disproportionately affected by long standing structural inequalities and systemic racism. How educational institutions engage with Indigenous families during and beyond these challenging times can either support self-determination, cultural revitalization, and sustenance, or contribute to ongoing legacies of colonization, racism, and cultural erasure. This article provides a review of the literature on family-school-community leadership models and asks: How have conceptions of family-school-community leadership evolved over time and become more culturally responsive, sustaining and/or revitalizing? How might more culturally sustaining/revitalizing models of family and community engagement take seriously the historical legacies of colonization and family leadership in Indigenous communities? Key terms such as involvement, engagement, partnership, and activism are defined and a continuum of family-school-community leadership frameworks is presented which move from traditional paradigms to more culturally sustaining and revitalizing practices. Relevant literature is reviewed for each of these evolving models.